Advanced TexSy-C Nanocomposites for High-Performance Lithium Ion Batteries - Lu, Guolong; Ye, Chunnuan; Li, Wenyan; He, Xuedong; Chen, Guang; Li, Jun; Jin, Huile; Wang, Shun; Wang, Jichang (Frontiers in Chemistry, 2021)
This study is dedicated to expand the family of lithium-tellurium sulfide batteries, which have been recognized as a promising choice for future energy storage systems. Herein, a novel electrochemical method has been applied to engineer micro-nano TexSy material, and it is found that TexSy phases combined with multi-walled carbon nanotubes endow the as-constructed lithium-ion batteries excellent cycling stability and high rate performance. In the process of material synthesis, the sulfur was successfully embedded into the tellurium matrix, which improved the overall capacity performance. TexSy was characterized and verified as a micro-nano-structured material with less Te and more S. Compared with the original pure Te particles, the capacity is greatly improved, and the volume expansion change is effectively inhibited. After the assembly of Li-TexSy battery, the stable electrical contact and rapid transport capacity of lithium ions, as well as significant electrochemical performance are verified.